Charge-depletion-enhanced WSe2 quantum emitters on gold nanogap arrays with near-unity quantum efficiency - Cai, Hongbing (2024)
Achieving unity quantum efficiency in single-photon emitters (SPEs) is a holy grail in quantum information science. Through plasmonic coupling it is possible to increase the quantum efficiency of SPEs by increasing the radiative decay rate, but to approach unity quantum efficiency, non-radiative decay must be mitigated. Here we show that non-radiative decay in two-dimensional WSe2 quantum emitters can be electrically suppressed through charge depletion by using dual gate configurations under a large electric field. In this condition, for site-controlled SPEs in WSe2 coupled to gold nanogaps, the SPE transition quantum efficiency after gating is increased to 76.4 ± 14.6% on average, with some SPEs reaching near-unity (more than 90%) quantum efficiency. This study provides a new approach for tuning SPEs with an applied gate voltage and motivates further theoretical and experimental studies of SPE enhancement on vertically aligned nanogaps.